Premature ovarian insufficiency in female adolescent and young adult survivors of non-gynecological cancers: a population-based cohort study - Sydney B. Flatt; Amanda Baillargeon; Chad McClintock; Jessica Pudwell; Maria P. Velez (BMC, 2023)
Plain language summary Premature ovarian insufficiency is the onset of premature menopause in individuals less than 40-years-old. Previous research has shown that there is a higher risk of premature ovarian insufficiency in adolescent and young adult cancer survivors, due to the toxicity of cancer treatments on reproductive organs. Prior research was limited in its applicability by having small sample sizes, only including childhood cancer, excluding young adults, and studying fewer types of cancer. This study was conducted using a large population-based approach, on all females aged 15-39 years old with cancer in Ontario, Canada from 1995 to 2015. We found that there was nearly a 2.5 times greater risk of premature ovarian insufficiency in cancer survivors compared patients without cancer. Compared to patients without cancer, this risk was highest for survivors of leukemia (14 times higher risk), followed by breast cancer (4 times higher risk), lymphomas (2-4 times higher risk), and thyroid cancer (1.2 times higher risk). There is no increased risk in melanoma survivors. The risk was higher in individuals diagnosed with cancer at a later age (30-39 years), with a risk 3 times higher than the population without cancer, while a younger age of diagnosis (15-29 years) carries a risk only 1.75 times higher than the population without cancer. These results should help improve healthcare provider and patient understanding of the risk of premature ovarian insuficiency in young cancer survivors, and guide counseling at the time of cancer diagnosis and during survivorship on future reproductive function.